POSTGRADUATE STUDENTS’ STUDY MODE AND UTILIZATION OF MOBILE TECHNOLOGIES FOR LEARNING IN NIGERIA (Universitas Kuningan, 2019)
The study examines Postgraduate students’ utilization of mobile technologies for learning and find out the differences in the utilization of mobile technologies by postgraduate students based on their mode of study. The study was a descriptive method of the survey type. Eleven universities across South-west, Nigeria were involved based on accessibility. A total of 658 were sampled. Researchers designed questionnaire was used for data collection. Mean was used to answer the research questions while Analysis of Variance (ANOVA) was used to test the hypothesis. A coefficient reliability of 0.87 was obtained on the instrument. The finding among others were that, the Ph.D. postgraduate students utilize mobile technologies for learning and research more than other postgraduate students’ counter parts, and there was no significant difference among postgraduate student’ utilization of mobile technologies for learning and research purposes based on mode of study, with the p-value 0.79 which is greater than 0.05 alpha value. The study concluded that, the effective utilization of mobile technologies by postgraduates could be of immense benefit towards their learning within and outside the classroom settings and also facilitate their research knowledge and skills. It is however recommended among others that more orientation should be organized for all postgraduate students in other to bridge the gap in the differences between postgraduate students in their utilization of mobile technologies for learning.